Er,Cr:YSGG Laser Therapy for Drug-Induced Gingival Overgrowth: A Report of Two Case Series - Liu, Yumei; Peng, Qian; Liu, Binjie; Wang, Zhibin; Cao, Qiong (Frontiers in Surgery, 2022)
Background: Drug-induced gingival overgrowth is common but neglected in patients with systemic diseases medications until it seriously affects the quality of life. Methods: Initial periodontal treatment combined with waterlaser surgery was performed sequentially. Results: The therapeutic effect was good and there was no recurrence with good oral hygiene. Conclusion(s): Waterlaser equipment surgery as well as initial periodontal treatment required the operators are trained specifically, it brings about a tool for various oral diseases which is safer, more efficient and more comfortable.